Réponses

Meilleure réponse !
2014-04-07T13:50:49+02:00
1) E=-5(-3x+5)²+(9x-15)
E=-5(9x²-30x+25)+9x-15
E=-45x²+150x-125+9x-15
E=-45x²+159x-140

2) F=9x+15
F=-3(-3x+5)

3) E=-5(-3x+5)²-3(-3x+5)
E=(5-3x)(-5(5-3x)-3)
E=(5-3x)(-25+15x-3)
E=(5-3x)(15x-28)

4a) si x=0 on utilise le 1)
E=-45*0+159*0-140=-140
4b) si x=5/3 on utilise le 3)
E=(5-3*5/3)(15*5/3-28)=(5-5)*(15*5/3-28)=0
4c) si x= \sqrt{2} on utilise le 1)
E=-45*2+159 \sqrt{2} -140
E=-230+159 \sqrt{2}

5) Un produit est nul si l'un des facteurs est nul donc
E=0
⇔(5-3x)(15x-28)=0
⇔5-3x=0 ou 15x-28=0
⇔x=5/3 ou x=28/15

5/3+28/15=25/15+28/15=53/15